Integrating Trauma-Informed Care Post-ACE Screening in School Settings - McNeely, Tonya (My University, 2025)
Exposure to Adverse Childhood Experiences (ACEs) is strongly associated with negative academic, behavioral, and health outcomes in school-aged children. This quality improvement project assessed the feasibility of integrating ACE screening into a school-based support model by training student support staff from a nonprofit organization in trauma-informed care.